Over-expression of PRAS40 enhances insulin sensitivity in skeletal muscle. (May 2014) - Wiza, Claudia; Chadt, Alexandra; Blumensatt, Marcel; Kanzleiter, Timo; Herzfeld De Wiza, Daniella; Horrighs, Angelika; Mueller, Heidi; Nascimento, Emmani B.M.; Schürmann, Annette; Al-Hasani, Hadi; Ouwens, D. Margriet
Abstract Context: Silencing proline-rich Akt substrate of 40-kDa (PRAS40) impairs insulin signalling in skeletal muscle. Objective: This study assessed the effects of over-expressing wild type or mutant AAA-PRAS40, in which the major phosphorylation sites and mTORC1-binding site were mutated, on insulin signalling in skeletal muscle. Results: Over-expression of WT-PRAS40, but not AAA-PRAS40, impaired the insulin-mediated activation of the mTORC1-pathway in human skeletal muscle cells (hSkMC). However, insulin-mediated Akt-phosphorylation was increased upon over-expression of WT-PRAS40 both in hSkMC and mouse skeletal muscle. Also over-expression of AAA-PRAS40 had an insulin-sensitizing effect, although to a lesser extent as WT-PRAS40. The insulin-sensitizing effect associated with increased IRS1 protein abundance and inhibition of proteasome activity. Finally, over-expression of WT-PRAS40 reversed hyperinsulinemia-induced insulin resistance. Conclusion: This study identifies PRAS40 as a regulator of insulin sensitivity in hSkMC. In contrast to the mTORC1-pathway, the insulin-sensitizing action of PRAS40 occurs independent of binding of PRAS40 to the mTORC1-complex.